Ecotoxicological impact of two soil remediation treatments in Lactuca sativa seeds - Rede, Diana (2016)
Pharmaceuticals have been identified as environmental emerging pollutants and are present in different compartments, including soils. Chemical remediation showed to be a good and suitable approach for soil remediation, though the knowledge in their impact for terrestrial organisms is still limited. Therefore, in this work, two different chemical remediation treatments (Fenton oxidation and nanoremediation) were applied to a soil contaminated with an environmental representative concentration of ibuprofen (3 ng g-1). The phytotoxic impact of a traditional soil remediation treatment (Fenton oxidation) and of a new and more sustainable approach for soil remediation (nanoremediation using green nano-scale zerovalent iron nanoparticles (nZVIs)) was evaluated in Lactuca sativa seeds. Percentage of seed germination, root elongation, shoot length and leaf length were considered as endpoints to assess the possible acute phytotoxicity of the soil remediation treatments as well as of the ibuprofen contaminated soil. Both chemical remediation treatments showed to have a negative impact in the germination and development of lettuce seeds, exhibiting a reduction up to 45% in the percentage of seed germination and a decrease around 80% in root elongation comparatively to the contaminated soil. These results indicate that chemical soil remediation treatments could be more prejudicial for terrestrial organisms than contaminated soils.